Ant-like sac spiders from Jinyun Mountain Natural Reserve of Chongqing, China (Araneae: Corinnidae) - Wang, Lu-Yu; Zhang, Feng; Zhang, Zhi-Sheng (Zootaxa, 2012)
Eight corinnid species were collected from the Jinyun Mountain Natural Reserve: Corinnomma severum (Thorell, 1877)(male, female), Otacilia komurai (Yaginuma, 1952) (male, female), O. longituba sp. nov. (male, female), O. taiwanica(Hayashi & Yoshida, 1993) (male, female), Phrurolithus hamatus sp. nov. (male, female), P. zongxu sp. nov. (male,female), Trachelas japonicus Bösenberg & Strand, 1906 (male, female) and T. sinensis Chen, Peng & Zhao, 1995 (female). Morphological illustrations and photos of all species and descriptions of new species are given.